High, medium and low pressure assemblages from the Czech part of the Kralovsky Hvozd Unit (KHU) in the Moldanubian Zone of SW Bohemia - Baburek,J. (Journal of the Czech Geological Society, 1995)
The Kralovsky Hvozd Unit (KHU), conventionally belonging to the Monotonous group of the Moldanubicum, shows an important lithological heterogeneity. Thus, position of isograds based on index minerals (Vejnar 1963, 1991) was revised from this point of view. The first entry of staurolite follows the main lithological boundaries between metapelitic rocks and those of more greywacke character. The main three lithological segments of the KHU that have been distinguished preserve different PT-evolution stages. The lithological variegated northern segment underwent a higher-pressure event (450 °C/10 kb). This segment conserves metamorphic record without equivalence in the whole Moldanubian Zone. Taking into account the spatial relation of the rocks bearing HP/LT assemblages to the Central Bohemian Fault, an allochtonous position of at least parts of this northern segment seems to be probable. On the Bavarian side, Silurian microspores have been found in low-grade rocks at similar structural level (Reitz 1992). Nevertheless, the possibility, that a specific event of Moldanubian history has been here preserved, cannot be completely excluded. The SE-segment of gneisses of greywacke affinity conserves a progressive Barrovian trend ranging from 500 °C/5.5 kb to 590 °C/6.5 kb and the SW-segment of metapelites shows the subsequent low-pressure overprinting ranging from 525 °C/1.5 kb to 575 °C/2 kb. The very high heat flow estimated from the PT-calculations witnesses an exclusive contact (periplutonic) kind of metamorphism in this segment.
Keywords: Metamorphism of pelitic rocks; low-grade metamorphism; medium-grade metamorphism; low-pressure metamorphism; medium- to high-pressure metamorphism; phengite barometry; petrogenetic grid; bulk rock chemistry; Variscides; Moldanubian Zone